IMPROVEMENT OF MECHANISMS OF CREATIVE SELF-DEVELOPMENT OF FUTURE TEACHERS (Web of Teachers: Inderscience Research, 2025)
This article is devoted to improvement of mechanisms of creative self-development of future teachers in the system of higher pedagogical education. The main mechanisms of professional and creative self-development of future teachers are considered.